2009
DOI: 10.5195/ijt.2009.868
|View full text |Cite
|
Sign up to set email alerts
|

Wheelchair Seating Assessment and Intervention: A Comparison between Telerehabilitation and Face-to-Face Service

Abstract: Abstr actThis study compared outcomes of wheelchair seating and positioning interventions provided by telerehabilitation (n=10) and face-to-face (n=20; 10 in each of two comparison groups, one urban and one rural). Comparison clients were matched to the telerehabilitation clients in age, diagnosis, and type of seating components received. Clients and referring therapists rated their satisfaction and identified if seating intervention goals were met. Clients recorded travel expenses incurred or saved, and all t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 25 publications
0
45
0
2
Order By: Relevance
“…In a well-designed casecontrol study (N=29), wait time for provision of wheelchair and seating assessment differed significantly for wheelchair users who live 'out of region' (i.e., very remotely from specialist centers) for IP-WS assessment (F(2, 27)=3.90, P=.03) compared to wheelchair users who lived locally (56 days v 29 days respectively). However no difference in wait times was observed irrespective of geographic location of wheelchair user for patients receiving tele-WS assessment (32 days) [24]. Notably, 'out of region' wheelchair-users in this study reported that through tele-WS assessment they accessed specialist assessment services otherwise not available to them, due to where they lived.…”
Section: Evidence Of Effectivenessmentioning
confidence: 73%
See 4 more Smart Citations
“…In a well-designed casecontrol study (N=29), wait time for provision of wheelchair and seating assessment differed significantly for wheelchair users who live 'out of region' (i.e., very remotely from specialist centers) for IP-WS assessment (F(2, 27)=3.90, P=.03) compared to wheelchair users who lived locally (56 days v 29 days respectively). However no difference in wait times was observed irrespective of geographic location of wheelchair user for patients receiving tele-WS assessment (32 days) [24]. Notably, 'out of region' wheelchair-users in this study reported that through tele-WS assessment they accessed specialist assessment services otherwise not available to them, due to where they lived.…”
Section: Evidence Of Effectivenessmentioning
confidence: 73%
“…In relation to patient-centered outcomes of tele-WS assessment, research so far has focused on feasibility issues, with only two of the more recent studies [23,24] exploring its effectiveness in achieving patient-centered outcomes. All outcomes are reported in Table 3.…”
Section: Outcomes Measuredmentioning
confidence: 99%
See 3 more Smart Citations